Regional assessment of storm related overwash and breaching hazards on coastal barriers - Plomaritis, Theocharis A. (2019)
Coastal communities are threatened by the impact of severe storms that may cause significant loss of life and damage to properties. Among the main processes behind such impacts on coastal barriers are the occurrence of overwash and breaching during storm events. In order to estimate potential losses associated with a particular event, the above processes must be properly parameterized. Here, we propose a novel methodology to estimate overwash and breaching hazards suitable for a regional scale analysis (Ø 100 km). For the overwash hazard assessment, the method is based on the application of the approach developed by Donnelly (2008) that allows the parametrisation of the overwash hazard considering both flow velocity and flow depth. Moreover, the inland extension of the associated hazard, which is critical to assess subsequent vulnerability, can also be estimated following this methodology. The proposed method requires the selection of a runup formula validated for the study area, a storm beach profile, a runup lens angle, and a percolation constant for infiltration. To assess the breaching, hazard, a new multivariable evaluation is proposed that allows ranking the potential of breaching. The multivariable evaluation combines overwash and erosion hazards as well as their extensions with the main morphological characteristics of the barrier, resulting in the breaching hazard index, that ranks from 0 to 5 (no breaching to inlet formation). Inland breaching extension is also relevant for the vulnerability assessment. The breaching extension can be estimated using historical or contemporary analogues of the nearest flood deltas. The developed approaches were applied to Ancão Peninsula (Algarve, Portugal) as a demonstration example. The advantages of the present approach are: adaptability to various environments where overwash and/or breaching processes are important, time efficiency on evaluating overwash and breaching hazards, and the assessment of hotspot areas at a regional scale.